Analysis of the Prognostic Value and Gene Expression Mechanism of SHOX2 in Lung Adenocarcinoma - Li, Nanhong; Zeng, Yu; Tai, Min; Lin, Biyun; Zhu, Di; Luo, Yi; Ren, Xinle; Zhu, Xiaoying; Li, Lanlan; Wu, Hongrong; Huang, Jian (Frontiers in Molecular Biosciences, 2021)
Background Detection of SHOX2 methylation has been used to assist in the early diagnosis of lung cancer in many hospitals as SHOX2 may be important in the tumorigenesis of lung cancer. However, there are few studies on the mRNA expression, methylation, and molecular mechanism of SHOX2 in lung cancer. We aimed to explore the role of SHOX2 in lung adenocarcinoma (LUAD). Methods First, we examined the differential expression of SHOX2 mRNA and methylation in cancerous and normal tissues using databases. Second, we analyzed the relationship between SHOX2 expression and common clinical parameters in LUAD patients. Third, we further explored SHOX2 expression, mainly its factors and methylation. Finally, we screened the correlative-expressed genes to analyze the pathways from the Gene Ontology and Kyoto Encyclopedia of Genes and Genomes using DAVID. Results We found that the mRNA expression of SHOX2 was higher in multiple cancers, including LUAD and lung squamous cell carcinoma, than in normal tissues. Among LUAD patients, SHOX2 expression was higher in patients of a middle-young age, with smoking history, in advanced stages, and with nodal distant metastasis. In addition, our results showed that patients with high expression of SHOX2 are prone to recurrence, poor differentiation, and poor prognosis. We thus identified SHOX2 might be as an oncogene for LUAD progression. The main mechanism of the high expression of SHOX2 mRNA may be DNA methylation, followed by Copy Number Variation (CNV), but not by gene mutations in LUAD. Unexpectedly, we found that SHOX2 undergoes hypomethylation in the gene body instead of hypermethylation in the promoter. Additionally, SHOX2 has cross talk in PI3K−Akt signaling pathway and ECM−receptor interaction. Conclusion SHOX2 is highly expressed in most cancers. SHOX2 gene expression might be mainly regulated by methylation of its gene body in LUAD, and its high expression or hypomethylation indicates poor differentiation and poor prognosis. SHOX2 could be involve in PI3K-Akt and other important cancer-related signaling pathways to promote tumorigenesis.